Pengaruh Senam Kaki Diabetes Mellitus terhadap Kadar Gula Darah Penderita DM Tipe 2 di Wilayah Kerja Puskesmas Ciemas - Yeni Yulianti; Riyan Sulistiana Januari (Fakultas Kesehatan Universitas Muhammadiyah Sukabumi, 2021)
Diabetes Mellitus is a non-communicable metabolic disorder that affects several millions of people worldwide. One of the ways to manage type 2 DM is physical exercise. Physical exercise that can be done is foot exercises. The purpose of this study was to determine the effect of foot exercise on changes in blood sugar levels in patients with type 2 diabetes. This type of research was a quasi-experimental with a total sample of 18 people. The sampling technique used was purposive sampling. The instruments used are SOP and glukotest. Hypothesis testing using Paired sample t-test. The results of the study obtained a p-value of 0.000 which indicates that there is an effect of foot exercise on changes in blood sugar levels in patients with type 2 diabetes. The mean pre-test value is 218.22 and the post-test is 202.82 with a difference of 15.28. In conclusion, there is an effect of foot exercise on changes in blood sugar levels in patients with type 2 diabetes. It is hoped that this foot exercise can be used as non-pharmacological therapy for patients with type 2 diabetes, especially in lowering blood sugar levels.